School Culture and Management Strategies for Cultivating Religious Character at SMA Negeri 6 Kota Bengkulu - Fatma Wardah; Faras Cahaya Utami; Pera Perisla; Hengki Satrisno; Bambang Irawan (JMiE (Journal of Management in Education), 2024)
This study examines the role of school culture and management strategies in cultivating religious character among students at SMA Negeri 6 Kota Bengkulu. Employing a qualitative case study approach, data were collected through classroom observations, interviews with teachers, administrators, and students, as well as document analysis. Findings indicate that a positive school culture—comprising formal rules, informal interactions, rituals, and environmental cues—significantly influences students’ ethical behavior, spiritual awareness, and social responsibility. Management strategies, including curriculum integration, teacher professional development, leadership practices, extracurricular programs, and community engagement, reinforce cultural values and ensure consistent implementation. Observational and interview data show that alignment between school culture and management practices fosters higher levels of empathy, discipline, and moral reasoning. Challenges such as diverse student backgrounds and resource limitations are addressed through adaptive leadership, reflective practices, and collaborative approaches. The study concludes that a holistic integration of cultural and managerial strategies provides an effective framework for sustainable religious character development in secondary education.